Method for controlling lattice strain in zirconia
Patent Information
- Application Number
- CN202611485983.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]因此,现有技术中缺乏一种能够在降低氧空位相关缺陷干扰的同时,通过简便热历程调节氧化锆残余应变的方法,成为本领域亟待解决的技术问题
[0015]本发明与现有技术相比,具有以下有益效果:(1)通过选择F1或F2中间体确定初始畸变状态,再通过相同后处理获得相对低应变或高应变产物,使应变调控具有明确的制备路径,实现了在降低氧空位相关缺陷干扰的同时调节氧化锆的残余应变。(2)采用氧气饱和气氛中的石墨舟焦耳热处理,设备输出参数为30V和300A,8秒至12秒达到1000°C且不保温,单次加热与自然冷却过程为数分钟,热历程短,有效限制了高温结构重排和晶格弛豫,使氧空位相关顺磁信号淬灭的同时保留了不同程度的晶格应变。(3)以制备方法及其关键热历程为主体,表征仅用于验证调控结果,不将电催化性能或特定用途作为实施本方法的必要条件,方法通用性强。
Smart Images

Figure CN122977436A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of oxide material preparation, defect engineering and lattice strain control technology, and specifically relates to a method for controlling lattice strain in zirconium oxide. Background Technology
[0002] Lattice strain can alter interatomic spacing, local coordination, and electronic structure in oxides, making it a crucial structural factor for regulating material properties. The formation of oxygen vacancies and changes in their electronic occupancy states can be accompanied by displacement of neighboring atoms and local lattice distortion; therefore, defect manipulation can serve as a means of introducing strain. For zirconia, the formation of oxygen vacancies and changes in their electronic occupancy states can be accompanied by displacement of neighboring atoms and local lattice distortion. Zirconia with different oxygen vacancy charge states, F¹ and F² centers exhibit different electronic occupancy characteristics, and their local coordination environments can produce varying degrees of distortion. However, when strain is obtained through defect engineering, oxygen vacancies, charge states, and lattice distortion often change simultaneously. If subsequent heat treatment is performed, defect repair may be accompanied by lattice relaxation, grain growth, or phase changes, affecting the control of residual strain. Current material preparation still requires strain control schemes that are easy to operate, have short thermal histories, and can maintain comparability in both phase and size.
[0003] Therefore, the lack of a method in the prior art that can reduce the interference of oxygen vacancy-related defects while adjusting the residual strain of zirconia through a simple thermal process has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] The technical problem to be solved by this invention is that when defect engineering is used to introduce strain into zirconia, oxygen vacancies, charge states and lattice distortion often change simultaneously. If sufficient heat treatment is carried out afterward, defect repair may be accompanied by lattice relaxation, grain growth or crystal phase change, which affects the control of residual strain.
[0005] To address the aforementioned technical problems, this invention provides a method for controlling lattice strain in zirconium oxide, comprising the following steps: Step S100: Based on the target strain state, by adjusting the local electron supply environment during the zirconia formation process, a material with F... 1 Center or F 2 The central zirconia intermediate imparts lattice distortion to the zirconia intermediate that is related to the oxygen vacancy charge state. Step S200: Place the zirconium oxide intermediate in a graphite boat and introduce oxygen into the reaction space to saturate the sample with oxygen. Step S300: The graphite boat is energized for a short-term rapid heating, reaching 1000°C within 8 to 12 seconds. Heating is stopped after the target temperature is reached, without setting a constant temperature holding stage. The material is then allowed to cool naturally to obtain a zirconium oxide material with oxygen vacancy-related paramagnetic centers quenched and lattice strain preserved. Among them, F 1 F represents an oxygen vacancy center that has captured an electron. 2 This represents an oxygen vacancy center that has captured two electrons; the residual strain of zirconia materials can be adjusted by selecting zirconia intermediates with different oxygen vacancy charge states.
[0006] Further, step S100 includes: Step S110: Using Zr(OH)4 as a precursor and NH4Cl or NaCl as a salt template agent, the mass ratio of precursor to corresponding salt template agent is 1:20. NH4Cl and NaCl are used separately for two different preparation routes without being mixed. 100 mg Zr(OH)4 is ball-milled with 2.0 g NH4Cl or 2.0 g NaCl for 10 min, then heated to 500°C at a rate of 5°C / min and held at that temperature for 4 h. Using NH4Cl as the salt template agent, a product containing F is obtained. 2 The center F 2 -ZrO 2-x Intermediate, prepared using NaCl as a salt template agent, containing F 1 The center F 1 -ZrO 2-x Intermediate; In step S120, the obtained intermediate is washed with deionized water 3 to 4 times and dried at 100°C to remove soluble salts and residual washing water.
[0007] Further, in step S110, the Zr(OH)4 precursor is prepared as follows: Zr(NO3)4·5H2O is weighed and dissolved in deionized water, stirred in an oil bath at 70°C, ammonia is added dropwise until the pH is 8, stirred until a precipitate is formed, filtered under a solution temperature above 70°C, the filter cake is washed 2 to 3 times with deionized water, and dried at 100°C for 8 to 12 hours to obtain the Zr(OH)4 precursor.
[0008] Furthermore, in step S200, 100% oxygen is introduced into the reaction space to fill the reaction space containing the sample with oxygen, and the sample is kept in an oxygen atmosphere during the heating phase.
[0009] Furthermore, in step S300, the output parameters of the Joule heating equipment are 30V and 300A; the same graphite boat specifications, sample loading conditions, power output parameters, and Joule heating temperature-time program are used when preparing zirconia with different strains; the complete heating and cooling process takes several minutes.
[0010] Further, in step S100, F 2 -ZrO 2-x After processing the intermediate in steps S200 and S300, HStrained-ZrO2 is obtained, which is then used to obtain F 1 -ZrO 2-x The intermediate was processed through steps S200 and S300 to obtain LStrained-ZrO2; the high strain and low strain of HStrained-ZrO2 and LStrained-ZrO2 are relative states compared with each other under the same analytical conditions.
[0011] Furthermore, F was processed using the same Joule heating program. 2 -ZrO 2-x and F 1 -ZrO 2-x The two groups of zirconia obtained have the same main crystal phase and similar particle size, and have distinguishable strain differences; the microstrain of HStrained-ZrO2 is 0.40%, and the microstrain of LStrained-ZrO2 is 0.18%.
[0012] Furthermore, it also includes the verification of the modulation results: under comparable electron paramagnetic resonance testing conditions, confirming F 1 intermediate F 1 In the signal and F² intermediate with Zr 3+ The relevant paramagnetic signals were no longer distinguishable after Joule heating; X-ray diffraction peak broadening analysis confirmed that micro-strain of varying degrees still existed after processing.
[0013] Furthermore, the Williamson-Hall method was used to analyze the broadening of X-ray diffraction peaks, satisfying the following conditions: , in, For the diffraction peak width, Where is the Bragg angle, and K is the shape factor. Where λ is the X-ray wavelength, and D is the coherent diffraction size. The microstrain parameters were determined; and the microstrain and local strain distribution at the grain population scale were cross-validated by combining nanobeam electron diffraction, atomic-resolution high-resolution transmission electron microscopy images, and geometric phase analysis.
[0014] Furthermore, in step S300, in the zirconium oxide material obtained after natural cooling, the oxygen vacancy-related paramagnetic centers are quenched, while the lattice strain is retained. The lattice strain is confirmed by X-ray diffraction peak broadening and local lattice analysis.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) By selecting F 1 or F2 The intermediate determines the initial distortion state, and then obtains relatively low strain or high strain products through the same post-processing, so that the strain regulation has a clear preparation path, and realizes the adjustment of the residual strain of zirconia while reducing the interference of oxygen vacancy related defects. (2) The graphite boat Joule heat treatment in oxygen saturated atmosphere is adopted. The equipment output parameters are 30V and 300A. It reaches 1000°C in 8 to 12 seconds without holding. The single heating and natural cooling process takes several minutes. The thermal history is short, which effectively restricts high-temperature structural rearrangement and lattice relaxation, and quenches the oxygen vacancy related paramagnetic signal while retaining different degrees of lattice strain. (3) The preparation method and its key thermal history are the main body. The characterization is only used to verify the regulation results. Electrocatalytic performance or specific use is not taken as a necessary condition for implementing this method. The method has strong versatility. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the preparation process of the zirconium oxide lattice strain control method of the present invention.
[0017] Figure 2 This is a comparison chart of EPR before and after Joule heating for the two routes.
[0018] Figure 3 The HAADF-STEM and elemental distribution diagrams of HStrained-ZrO2 and LStrained-ZrO2 are shown.
[0019] Figure 4 The figures show the XRD and Williamson-Hall analyses of HStrained-ZrO2 and LStrained-ZrO2.
[0020] Figure 5 Nanobeam electron diffraction and atomic-resolution transmission electron microscopy images of HStrained-ZrO2 and LStrained-ZrO2.
[0021] Figure 6 GPA local strain analysis diagrams for HStrained-ZrO2 and LStrained-ZrO2.
[0022] Figure 7 XPS, XANES, and EXAFS analysis plots for HStrained-ZrO2 and LStrained-ZrO2. Detailed Implementation
[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0024] This application is based on F 1 and F2 The superscripts indicate that the oxygen vacancy has captured one electron and two electrons, respectively, in F. 1 F represents an oxygen vacancy center that has captured an electron. 2 The superscript indicates an oxygen vacancy center that has captured two electrons; the superscript does not indicate the valence state of zirconium. HStrained-ZrO2 and LStrained-ZrO2 are the sample names for relatively high-strain and relatively low-strain zirconium oxide, respectively.
[0025] Reference Figure 1 The present invention provides a method for controlling the lattice strain in zirconium oxide, comprising the following steps: Step S100: Based on the target strain state, by adjusting the local electron supply environment during the zirconia formation process, a material with F... 1 Center or F 2 The central zirconia intermediate imparts a lattice distortion to the zirconia intermediate that is related to the oxygen vacancy charge state. Step S200: Place the zirconium oxide intermediate in a graphite boat and introduce oxygen into the reaction space to saturate the sample with oxygen. In step S300, the graphite boat is energized for a short-term rapid heating, reaching 1000°C within 8 to 12 seconds. Heating is stopped after the target temperature is reached, without setting a constant temperature holding stage. The material is then allowed to cool naturally to obtain a zirconia material with oxygen vacancy-related paramagnetic centers quenched and lattice strain preserved.
[0026] The specific implementation methods of each step are explained in detail below with reference to the accompanying drawings.
[0027] Step S100, prepare F 1 Center or F 2 The central zirconium oxide intermediate; Step S100 uses Zr(OH)4 as a precursor and NH4Cl or NaCl as a salt template agent, with a precursor-to-corresponding salt template agent mass ratio of 1:20. NH4Cl and NaCl are used separately in two different preparation routes and are not mixed. Using NH4Cl as a salt template agent, a product containing F is obtained. 2 The center F 2 -ZrO 2-x Intermediate, prepared using NaCl as a salt template agent, containing F 1 The center F 1 -ZrO 2-x Intermediate.
[0028] Step S100 further includes the following sub-steps: Step S110: 100 mg Zr(OH)4 is ball-milled with 2.0 g NH4Cl or 2.0 g NaCl for 10 min, then heated to 500°C at a rate of 5°C / min and kept at that temperature for 4 h to obtain products containing F. 2 Center or F 1 The central zirconium oxide intermediate; In step S120, the obtained intermediate is washed with deionized water 3 to 4 times and dried at 100°C to remove soluble salts and residual washing water.
[0029] The considerations for using steps S110 to S120 are as follows: The local nitrogen-containing atmosphere formed by the thermal decomposition of NH4Cl differs from the NaCl template environment, thus creating different defect electron occupancy states in zirconium oxide. The NH4Cl route tends to form F... 2 At the center, the NaCl route tends to form F 1 Center. Washing and drying remove soluble salts to prevent residues from affecting subsequent Joule heat treatment.
[0030] Step S200: Oxygen saturated atmosphere treatment; In step S200, the zirconium oxide intermediate obtained in step S100 is loaded into the sample area of the graphite boat, and 100% oxygen is introduced into the reaction space to fill the reaction space where the sample is located with oxygen, and the sample is kept in an oxygen atmosphere during the heating stage.
[0031] Step S300: Short-time rapid Joule heat treatment; In step S300, the graphite boat is energized for a short-term rapid heating process. The Joule heating device is set to output 30V and 300A, allowing the sample to reach 1000°C within 8 to 12 seconds. Heating is stopped after the target temperature is reached, without setting a 1000°C constant temperature holding stage. The sample then cools naturally. The entire heating and cooling process takes several minutes.
[0032] The considerations for using step S300 are as follows: the oxygen-rich short-time heating process is used to promote the oxidation repair or passivation of oxygen vacancy-related defect states; no high-temperature holding stage is set to limit further high-temperature structural rearrangement. The oxygen vacancy-related paramagnetic signal is quenched after Joule heating, while the lattice strain does not have enough time to fully relax due to the extremely short thermal history, thus retaining varying degrees of residual strain.
[0033] With F 2 -ZrO 2-x After processing the intermediate in steps S200 and S300, HStrained-ZrO2 is obtained, which is then used to obtain F 1 -ZrO 2-xThe intermediate is processed through steps S200 and S300 to obtain LStrained-ZrO2. The high strain and low strain of HStrained-ZrO2 and LStrained-ZrO2 are relative states compared under the same analytical conditions.
[0034] Example 1: Preparation of Zr(OH)4 precursor. 6.87 g of Zr(NO3)4·5H2O was weighed and dissolved in 100 mL of deionized water. The solution was stirred in a 70°C oil bath. Ammonia was slowly added dropwise until the pH reached 8, and stirring continued to allow precipitation to form. The solution was filtered while hot. The filter cake was washed 2 to 3 times with deionized water and dried overnight at 100°C to obtain the Zr(OH)4 precursor.
[0035] Example 2, F for high strain paths 2 -ZrO 2-x Intermediate preparation. 100 mg of Zr(OH)₄ obtained in Example 1 and 2.0 g of NH₄Cl were weighed and mixed at a mass ratio of 1:20, and ball-milled for 10 min. The mixture was placed in a muffle furnace and heated to 500°C at a rate of 5°C / min, held for 4 h, and then cooled. The resulting product was washed 3 to 4 times with deionized water and dried overnight at 100°C to obtain F for subsequent high-strain pathways. 2 -ZrO 2-x Intermediate.
[0036] Example 3, F1-ZrO for low strain pathways 2-x Intermediate preparation. 100 mg of Zr(OH)₄ obtained in Example 1 and 2.0 g of NaCl were weighed and mixed at a mass ratio of 1:20, and ball-milled for 10 min. The mixture was placed in a muffle furnace and heated to 500°C at a rate of 5°C / min, held for 4 h, and then cooled. The mixture was washed 3 to 4 times with deionized water to remove NaCl, and dried overnight at 100°C to obtain F for subsequent low-strain pathways. 1 -ZrO 2-x Intermediate. Except for the template type, the precursor batch, ball milling, heat treatment, washing, and drying conditions were consistent with those in Example 2.
[0037] Example 4: Preparation of HStrained-ZrO2 by oxygen-enriched Joule heating. Weigh out the F obtained in Example 2... 2 -ZrO 2-x10 mg of the intermediate was loaded into the sample area of a graphite boat. 100% oxygen was introduced into the reaction space to create an oxygen-saturated atmosphere around the sample, and this atmosphere was maintained during the heating phase. The Joule heating apparatus was set to 30V and 300A to power the graphite boat, causing the sample to reach 1000°C within 8 to 12 seconds. Heating was stopped after reaching the target temperature; no holding phase was set, and the sample was allowed to cool naturally. After cooling, the sample was collected and labeled HStrained-ZrO2.
[0038] Example 5: Preparation of L-trained-ZrO2 by oxygen-enriched Joule heating. Using the F obtained in Example 3... 1 -ZrO 2-x F instead of Example 4 2 -ZrO 2-x Using the same sample volume, graphite boat specifications, oxygen conditions, heating process from 8 to 12 seconds to 1000°C, and no heat preservation followed by natural cooling, LStrained-ZrO2 was obtained. The remaining operations were the same as in Example 4.
[0039] Example 6: EPR verification of oxygen vacancy correlation signals before and after Joule heating. The EPR of F... 1 -ZrO 2-x F 2 -ZrO 2-x EPR tests were performed on the corresponding Joule thermal products, and the results are shown in [the table below]. Figure 2 Before processing, F 1 The route has a distinguishable F 1 Signal, F 2 The route has Zr 3+ The relevant paramagnetic signal, in which Zr 3+ The value represents trivalent zirconium ions. After Joule heating, the corresponding signals in both LStrained-ZrO2 and HStrained-ZrO2 disappeared, indicating that the oxygen vacancy-related paramagnetic signals in both pathways were rapidly quenched. These results demonstrate that, under an oxygen-saturated atmosphere and the same Joule heating program, the initial F... 1 Signals and Zr 3+ The relevant signals are no longer distinguishable after processing.
[0040] Example 7: Particle size, elemental distribution, and crystal phase comparability. HAADF-STEM observation and O and Zr elemental distribution characterization were performed on HStrained-ZrO2 and LStrained-ZrO2. The results are shown in […]. Figure 3 Both groups of samples exhibited similar nanoparticle morphologies, with particle sizes within a similar range in the field of view; O and Zr were uniformly distributed within the particle regions. XRD was used to compare the crystal phases of the two groups of products, and the results are shown in [Figure number missing]. Figure 4a and b. The positions and relative intensities of the main diffraction peaks of the two groups of samples are basically the same, indicating that the same main crystal phase is maintained after Joule heat treatment. Figure 4 In the local diffraction peaks shown in c and d, the FWHM of HStrained-ZrO2 is 0.78°, while that of LStrained-ZrO2 is 2.9°, with the former exhibiting a more pronounced diffraction peak broadening.
[0041] Example 8, Williamson-Hall global-scale microstrain analysis. Multiple diffraction peaks belonging to the same bulk crystalline phase were selected from two sets of samples. Peak widths were obtained using the same peak shape and background model, and uniformly expressed in radians. The Williamson-Hall method was used to separate coherent diffraction size broadening and strain broadening, satisfying: , in, For the diffraction peak width, Where is the Bragg angle, and K is the shape factor. Where λ is the X-ray wavelength, and D is the coherent diffraction size. These are micro-strain parameters. Both sets of samples used the same peak width definition, fitting peak selection, and fitting method. x-axis A linear fit is performed on the ordinate, and the slope corresponds to the microstrain. y-intercept corresponding The Williamson-Hall fitting results are shown in [link to results]. Figure 4 e, f. The microstrains of HStrained-ZrO2 and LStrained-ZrO2 are approximately 0.40% and 0.18%, respectively, indicating that under conditions of comparable host crystalline phase and particle size, the former retains a higher overall statistical microstrain.
[0042] Example 9, Nanobeam Electron Diffraction and Atomic-Resolved Structure Analysis. Nanobeam electron diffraction and atomic-resolution high-resolution transmission electron microscopy analyses were performed on HS-trained-ZrO2 and LS-trained-ZrO2. The results are shown in [Figure number missing]. Figure 5 . Figure 5 The diffraction spots of HStrained-ZrO2 shown in figure a exhibit more pronounced broadening and dispersion characteristics. Figure 5 The diffraction spots of LStrained-ZrO2 shown in b are relatively concentrated and regular, indicating that the former has a wider distribution range of lattice spacing and local orientation. Figure 5 c and d show the atomic arrangement of the two samples, respectively. The atomic pillar positions and lattice period of HStrained-ZrO2 show obvious local fluctuations, while the atomic arrangement of LStrained-ZrO2 is relatively regular.
[0043] Example 10, GPA Local Strain Analysis. Geometric phase analysis was performed on atomic-resolved images of HS-trained-ZrO2 and LS-trained-ZrO2. The displacement field was obtained using the same calibration rules, and the local strain tensor components were calculated. , , , Where u represents the displacement relative to the selected reference lattice. Both sets of samples employed consistent crystal orientation and coordinate definitions, reciprocal vector selection, Fourier masks, reference regions, drift handling, and statistical rules to ensure comparability of results. GPA analysis results are shown below. Figure 6 . Figure 6 a and b provide the values for HS-trained-ZrO2 and LS-trained-ZrO2, respectively. , and Three-dimensional distribution. HStrained-ZrO2 exhibits more pronounced local fluctuations across all three strain components, while the strain field of LStrained-ZrO2 is relatively flat. Figure 6 The `ce` parameter displays the frequency distribution and Gaussian fit of the three strain components. Compared to LStrained-ZrO2, HStrained-ZrO2... , and The distribution has broadened significantly.
[0044] Example 11: XPS, XANES, and EXAFS electronic structure and local structure analysis. XPS, Zr K-edge XANES, and EXAFS were used to compare the electronic structure and local coordination of the two groups of Joule thermal products. The results are shown in [Figure 11]. Figure 7 . Figure 7 The Zr3d XPS spectra shown in figure a exhibit a resolvable binding energy shift between the two groups of samples. Figure 7 The Zr K-edge XANES spectra shown in b have similar overall profiles, with slight, reproducible energy and spectral shape differences near the absorption edge. Figure 7 The Zr K-edge EXAFS Fourier transform spectra shown in c all exhibit Zr-O and Zr-Zr related coordination peaks, but the corresponding peak intensities and shapes differ. XPS, XANES, and EXAFS results indicate that the two groups of samples maintain the same host crystal phase while exhibiting distinguishable differences in electronic structure and local coordination.
Claims
1. A method for controlling the lattice strain in zirconium oxide, characterized in that, Includes the following steps: Step S100: By adjusting the local electron supply environment during the zirconium oxide formation process, a zirconium oxide with F... 1 Center or F 2 The central zirconia intermediate imparts lattice distortion to the zirconia intermediate that is related to the oxygen vacancy charge state. Step S200: Place the zirconium oxide intermediate in a graphite boat and introduce oxygen into the reaction space to saturate the sample with oxygen. Step S300: The graphite boat is energized for a short-term rapid heating, reaching 1000°C within 8 to 12 seconds. Heating is stopped after the target temperature is reached, without setting a constant temperature holding stage. The material is then allowed to cool naturally to obtain a zirconium oxide material with oxygen vacancy-related paramagnetic centers quenched and lattice strain preserved. Among them, F 1 F represents an oxygen vacancy center that has captured an electron. 2 This represents an oxygen vacancy center that has captured two electrons; the residual strain of zirconia materials can be adjusted by selecting zirconia intermediates with different oxygen vacancy charge states.
2. The method for controlling lattice strain in zirconium oxide according to claim 1, characterized in that, Step S100 includes: Step S110: Using Zr(OH)4 as a precursor and NH4Cl or NaCl as a salt template agent, the mass ratio of precursor to corresponding salt template agent is 1:
20. NH4Cl and NaCl are used separately for two preparation routes without being mixed. Zr(OH)4 and NH4Cl or NaCl are ball-milled at a mass ratio of 1:20 for 5 to 15 minutes, then heated to 450°C to 550°C at a rate of 3°C / min to 7°C / min and held at that temperature for 3 to 5 hours. Using NH4Cl as the salt template agent, a product containing F is obtained. 2 The center F 2 -ZrO 2-x Intermediate, prepared using NaCl as a salt template agent, containing F 1 The center F 1 -ZrO 2-x Intermediate; In step S120, the obtained intermediate is washed with deionized water 3 to 4 times and dried at 100°C to remove soluble salts and residual washing water.
3. The method for controlling lattice strain in zirconium oxide according to claim 2, characterized in that, In step S110, the Zr(OH)4 precursor is prepared as follows: Zr(NO3)4·5H2O is weighed and dissolved in deionized water, stirred in an oil bath at 60°C to 80°C, ammonia is added dropwise until the pH is 7.5 to 8.5, stirred until a precipitate forms, filtered under a solution temperature of 60°C to 80°C or higher, the filter cake is washed 2 to 3 times with deionized water, and dried at 100°C for 6 to 14 hours to obtain the Zr(OH)4 precursor.
4. The method for controlling lattice strain in zirconium oxide according to claim 1, characterized in that, In step S200, oxygen with a volume fraction of 95% to 100% is introduced into the reaction space to fill the reaction space containing the sample with oxygen, and the sample is kept in an oxygen atmosphere during the heating stage.
5. The method for controlling lattice strain in zirconium oxide according to claim 1, characterized in that, In step S300, the output parameters of the Joule heating equipment are 20V to 40V and 200A to 400A; the same graphite boat specifications, sample loading conditions, power output parameters and Joule heating temperature-time program are used when preparing zirconia with different strains; the complete heating and cooling process takes several minutes.
6. The method for controlling lattice strain in zirconium oxide according to claim 1, characterized in that, In step S100, F 2 -ZrO 2-x After processing the intermediate in steps S200 and S300, HStrained-ZrO2 is obtained, which is then used to obtain F 1 -ZrO 2-x The intermediate was processed through steps S200 and S300 to obtain LStrained-ZrO2; the high strain and low strain of HStrained-ZrO2 and LStrained-ZrO2 are relative states compared with each other under the same analytical conditions.
7. The method for controlling lattice strain in zirconium oxide according to claim 6, characterized in that, F was processed using the same Joule thermal program. 2 -ZrO 2-x and F 1 -ZrO 2-x The two groups of zirconia obtained have the same main crystal phase and similar particle size, and have distinguishable strain differences; the microstrain of HStrained-ZrO2 is greater than that of LStrained-ZrO2.
8. The method for controlling lattice strain in zirconium oxide according to claim 1, characterized in that, It also includes verification of the modulation results: confirming F under comparable electron paramagnetic resonance testing conditions. 1 intermediate F 1 In the signal and F² intermediate with Zr 3+ The relevant paramagnetic signals are no longer distinguishable after Joule heating, Zr 3+ The sample represents trivalent zirconium ions; X-ray diffraction peak broadening analysis confirmed that micro-strain of varying degrees still existed after treatment.
9. The method for controlling lattice strain in zirconium oxide according to claim 8, characterized in that, X-ray diffraction peak broadening analysis was performed using the Williamson-Hall method, which satisfies: , in, For the diffraction peak width, Where is the Bragg angle, and K is the shape factor. Where λ is the X-ray wavelength, and D is the coherent diffraction size. The microstrain parameters were determined; and the microstrain and local strain distribution at the grain population scale were cross-validated by combining nanobeam electron diffraction, atomic-resolution high-resolution transmission electron microscopy images, and geometric phase analysis.